KAJIAN PRANATA MANGSA SEBAGAI PEDOMAN PENANGKAPAN IKAN DI SAMUDRA HINDIA SELATAN JAWA - Suwarman Partosuwiryo (Universitas Gadjah Mada, 2013)
Pranata mangsa is one form of local wisdom and cultural heritage whisch is slowly forgotten and should remain preserved and developed using scientiﬁc principles. This study was aims to assess the suitability of the pranata mangsa that have been used in the ﬁeld, examines the differences in the catch per effort and incomes between ship captain who use the pranata mangsa, who only occasionally use the pranata mangsa and do not use pranata mangsa. Primary and secondary data collection was conducted using a survey method. Determination of the respondents conducted by proportional stratiﬁed random sampling. The primary data obtained from interviews with respondents in the form of data signs of nature, types of ﬁsh cathced, ﬁshing gear, ﬁshing trip and production data. Secondary data were obtained from the reference form the provincial ﬁsheries statistics (East Java, Yogyakarta, Central Java), Fishery Port (Prigi, Sadeng, Cilacap) and Bakosurtanal. The study was conducted in the Indian Ocean in the southern of Java. The results showed that the natural signs of pranata mangsa that have been used was suitable in Prigi and Cilacap and were less suitable for Sadeng. The catch per unit effort from ship that did not used pranata mangsa was higher (5829.14 kg/ship/year) than ship that used the pranata mangsa (5219.79 kg/ship/year) and ship that only occasionally used the pranata mangsa (4,890.74 kg/ship/year). Revenue of ship that used pranata mangas (IDR. 196,282,199.00/ships/year) was higher than the income from ship that did not used the pranata mangasa (IDR. 131,145,173.00/ ships/year) and from ship that only occasionally using institutions prey (IDR. 111,405,847.00/ships/year). Pranata mangsa that had been used need improvements to be used in the Indian Ocean in the Southern of Java. Improved pranata mangsa need to be socialized in order to increase catch per unit effort and income of the ship captain, as well as the need for additional of more suitable ﬁshing gear.